WOMEN’S EDUCATION IN WESTERN SIBERIA (XIX – EARLY XX CENTURY): PROBLEMS OF THE FORMATION AND PECULIARITIES OF THE DEVELOPMENT - Antilogova L. N.; Makarova N. S.; Orlova L. N.; Petrusevich A. A.; Dyrka Stefan (Scientific Journal of Pedagogy and Economics, 2019)
The article justifies the relevance of considering the history of the establishment and operation of women’s educational institutions in Western Siberia throughout the 19th and early 20th centuries. Based on the study of published and archival materials, the article concluded, that there are prerequisites and theoretical ideas and practices, which developed in the Russian Empire in the XVIIII century to change the social status, cultural and educational potential of the women.